The in-service program of primary school teachers in Khuzistan, Iran - Marashi, Sied Ali Akbar 1935-
The purpose of the study is to determine the aims and objectives of the in-service training of primary teachers in Khuzistan in an attempt to highlight the strengths and weaknesses of the present program and to make suggestions and recommendations to make the program more effective. The study aims to serve as a basis for the improvement of the in-service programs including such aspects as planning, organizations, and implementations.